Root cause analysis of large scale application testing results - Opmanis, Rūdolfs; Ķikusts, Paulis; Opmanis, Mārtiņš (My University, 2015)
In this paper we present a new root cause analysis algorithm for discovering the most likely causes of the differences found in testing results of two versions of the same software. The problematic points in test and environment attribute hierarchies are presented to the user in compact way which in turn allows to save time on test result processing. We have proven that for clearly separated problem causes our algorithm gives exact solution. Practical application of described method is discussed.
Keywords: Root cause analysis, regression testing, hierarchy graphs.